(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Schizophrenia is ranked by the World Health Organization as one of the top ten illnesses contributing to global burden of disease, commonly associated with impairment in social and occupational functioning. It is defined by abnormalities in one or more of the five domains including delusions, hallucinations, disorganized thinking (speech), grossly disorganized or abnormal motor behaviour (including catatonia) and negative symptoms. A 40-year-old female patient was admitted in the Government Ayurveda Research Institute for Mental Health and Hygiene, Kottakkal, with agitation, anger, harming tendencies along with nudity for 2 months. There were suicidal ideations and escaping tendencies. In Ayurveda, Unmada is the umbrella term where almost all psychotic features are enlisted. Unmada is defined as perversion in Manas, Budhi, Samjnajnana, Smruthi, Bhakthi, Seela, Cheshta and Achara. Management of Unmada is based on the predominance of dosha involved in the pathogenesis. Sodhana, Samana and Satwavajaya are the 3 important treatment modalities used in management of Unmada. Sodhana procedure is foremost important in management of Unmada. The patient was treated on an IP level with a combination of Ayurvedic internal medications and procedures for 30 days. The treatment protocol including Sirodhara, Snehapana, Virechana, Vasti and Nasya was administered. PANSS scale was used to evaluate the symptoms before and after the treatment. There was a significant reduction in score from 115 to 45 after the intervention. This case report shows the importance of Ayurveda in the effective management of schizophrenia.